EVALUASI PROGRAM SISTEM INFORMASI PENILAIAN (SIP) BANDUNG JUARA DI BAGIAN TATA PEMERINTAHAN SEKRETARIAT DAERAH KOTA - FAUSTINE, ELIIKA DEWI (Prodi Administrasi Publik FISIP UNPAS, 2021)
Every government either central or regional is often required to always innovate, especially in the activities of qualified public servants. One of them is innovation whose activities are spread across each region in the city of Bandung is the Assessment Information System (SIP) Bandung Juara, which is a program built to assess the performance results of each camat and lurah in public service, the implementation of evaluation is measured based on the results of the activity report uploaded to the SIP Bandung Juara website, camat and lurah evaluation activities have several stages to get the final results of the assessment. The purpose of this research is to analyze and describe the Evaluation of The (SIP) BDG Juara Program in the Governance Section of the Bandung City Regional Secretariat to know, examine more deeply the problems, achievements, as well as the way of the evaluation process in the Bandung Champion SIP Program in carrying out services and identify the advantages of its shortcomings, therefore the focus on the problem is on the evaluation of the program. The research method used is qualitative with a descriptive approach. Data collection techniques are used with litelatur studies, observations, documents and interviews. To measure the evaluation of Program SIP BDG Juara researchers use the Program Evaluation Theory which has indicators Of Evaluation Context, Evaluation Input, Evaluation Process, Evaluation Product (CIPP). This research, has problems in performance has not been maximal, citizen assessment activities are not realized.